A new species, new synonymy, and notes on Paravelia Breddin (Hemiptera: Heteroptera: Veliidae) - Rodrigues, Higor Daniel Duarte; Moreira, Felipe Ferraz Figueiredo (Papéis Avulsos de Zoologia, 2016)
The broad-shouldered water strider Paravelia cunhai sp. nov. is described and illustrated based on material from the state of Pará, northern Brazil. The new species can be distinguished from all other species in this genus mainly by the dark color of the head and pronotum, absence of pruinosity or silvery pubescence on the anterior lobe of pronotum, maculae pattern on the fore wings, hind femur with row of 22 spines on mesal margin, and general shape of the paramere. This new species was collected in a pool inside a cave without incident light, a habitat recorded for the genus only recently, which reinforces the hypothesis that some species of Paravelia have troglophilic habits. In addition, a photograph of the dorsal habitus and notes concerning P. juruana Polhemus & Polhemus are provided, and P. cupariana Polhemus & Polhemus syn. nov. is proposed as a junior synonym of P. spinifera Polhemus & Polhemus.